Investigating the Role of Islamic Finance Literacy on Youths’ Economic Empowerment in Nigeria - Alaka, Abdullahi; Kewulere, Adam; Emiola, Habeeb (Li Falah: Journal of Islamic Economics and Business, 2025)
This study investigates the role of Islamic finance literacy in promoting economic empowerment among youths in Nigeria. Despite growing interest in Islamic finance, there remains a notable gap between theoretical understanding and practical application among Nigerian youth. The research identifies this gap as an obstacle to meaningful economic empowerment, especially in rural areas. A structured questionnaire was employed to gather data from a diverse sample of young respondents across Nigeria, assessing their awareness, understanding, and practical engagement with Islamic finance principles. The findings reveal that while many youths value the ethical and financial principles of Islamic finance, a lack of exposure and institutional support significantly limits their ability to leverage these tools for economic advancement. Notably, responses from urban areas were more informed, highlighting the need for inclusive strategies that target rural populations. The study finds strong correlations between Islamic finance literacy and youth empowerment outcomes, revealing the importance of integrated educational approaches. The research contributes new insights to the field by advocating for strategic collaboration between educational and Islamic finance institutions to develop inclusive literacy programs. It concludes that effective Islamic finance education can catalyze sustainable youth economic empowerment in Nigeria.